Electrically Actuated Hydraulic Solids1 . Issue 10 (1st September 2016) - Lipton, Jeffrey Ian; Angle, Sarah; Banai, Rona Elinor; Peretz, Eliad; Lipson, Hod
Abstract : The authors introduce a new class of electrically‐actuated soft materials. Electro‐active hydraulic solids (EAHSs) are comprised of numerous microscale phase change capsules embedded inside a conductive elastomer matrix which replicate traditional wax actuators in a massively parallel fashion. EAHS can generate forces and stress densities that exceed traditional electroactive actuators. For example, a 14 mm diameter 50 mm long cylinder can generate 4 500 N force and have over 3% strain. The authors describe a simple method for fabricating EAHS and demonstrate their compatibility with a wide range of manufacturing processes including additive manufacturing, subtractive manufacturing, and forming. Abstract : The authors introduce a new class of electrically actuated soft materials which can generate forces and stress densities that exceed traditional electroactive actuators. For example, a 14 mm diameter 50 mm long cylinder can generate 4 500 N of force while being less dense than water.